CONCURSO PÚBLICO PARA DIRETOR NA ESCOLA ESTADUAL PAULISTA: EXPECTATIVAS DOS ÓRGÃOS CENTRAIS DO ENSINO E CONCEPÇÕES DE DIRETORES - Hojas, Viviani Fernanda [UNESP] (Faculdade de Educação da Universidade Federal de Minas Gerais, 2015)
From the analysis of notices and tests of public contests to fill the position of school principal performed in state schools of São Paulo State and from the conceptions of directors, this article seeks to identify the expectations of central bodies of education regarding the role of these professionals and the administrative thought that supposedly guided and/or directs the administration of public paulista schools. The study of the notices and tests allowed observing that the desired profile for the school principal has changed significantly over time under the influence of political, economic, social and educational aspects. The investigation of the conceptions of directors, in turn, seems to rekindle the need to build a specific theory for the school administrative activity.

A partir da análise dos editais e das provas dos concursos públicos para provimento do cargo de diretor de escola realizados na rede estadual de ensino de São Paulo e das concepções de diretores, este artigo pretende identificar as expectativas dos órgãos centrais de ensino em relação à atuação desses profissionais e o pensamento administrativo que supostamente orientou e/ou orienta a administração das escolas públicas paulistas. O estudo dos editais e das provas permitiu observar que o perfil almejado para diretor de escola sofreu alterações significativas ao longo do tempo sob influência de aspectos políticos, econômicos, sociais e educacionais. A investigação das concepções dos diretores, por sua vez, parece reacender a necessidade de construção de uma teoria específica para a atividade administrativa escolar.
PUBLIC CONTEST FOR SCHOOL PRINCIPAL AT PAULISTA STATE SCHOOL:EXPECTATIONS OF THE TEACHING CENTRAL ORGANS AND CONCEPTIONS OFDIRECTORS
Keywords: School Administration; School principal; Public contest.; Administração Escolar; Diretor de escola; Concurso público.